Sicker Patients for Liver Transplantation: Meld, Meld Sodium, and Integrated Meld's Prognostic Accuracy in the Assessment of Posttransplantation Events at a Single Center from Argentina. (28th September 2013) - Piñero, Federico; Marciano, Sebastián; Villamil, Alejandra; Bandi, Juan; Casciato, Paola; Galdame, Omar; Giannasi, Sergio; de Santibañes, Eduardo; Gadano, Adrian
Abstract : Background . MELD or MELD sodium promotes sicker patients for earlier liver transplantation (LT); the balance between pre- and post-LT outcomes is still controversial. Aim . To compare MELD and related scores' risk assessment of short-term morbidity and mortality after LT. Methods . We included only transplanted cirrhotic patients from 6/2005 to 6/2010 (N = 152 ). Immediate pre-LT MELD, integrated MELD (iMELD), and two MELD sodium formulas " MELD Na1 " and " MELDNa2 " were calculated. Results . Pre-LT scores for nonsurvivors were higher than those for survivors: MELD (28 ± 8 versus 22 ± 7, P = 0.005 ), MELD Na1 (33 ± 8 versus 27 ± 10, P = 0.039 ), and iMELD (51 ± 6 versus 46 ± 8, P = 0.018 ). Patient survival assessment was performed by AUROC analysis (95% CI): MELD 0.694 (0.56–0.82; P = 0.006 ), MELD Na1 0.682 (0.56–0.79; P = 0.046 ), MELD Na2 0.651 (0.54–0.76; P = NS ), and iMELD 0.698 (0.593–0.80; P = 0.022 ). Patients with MELD ≥25 points had longer intensive care stay (mean 10 versus 7 days, P = 0.015 ) and longer mechanical ventilatory support (5.4 versus 1.9 days, P = 0.022 ). Conclusions . The addition of serum sodium to MELD does not improve assessment of mortality after LT. Patients with higher MELD may preclude higher morbidity after transplantation.